The impact of childhood deprivation on adult neuropsychological functioning is associated with ADHD symptom persistence. Issue 15 (18th November 2021) - Golm, Dennis; Sarkar, Sagari; Mackes, Nuria K.; Fairchild, Graeme; Mehta, Mitul A.; Rutter, Michael; ,; Sonuga-Barke, Edmund J.
Abstract: Background: Institutional deprivation in early childhood is associated with neuropsychological deficits in adolescence. Using 20-year follow-up data from a unique natural experiment – the large-scale adoption of children exposed to extreme deprivation in Romanian institutions in the 1980s –we examined, for the first time, whether such deficits are still present in adulthood and whether they are associated with deprivation-related symptoms of attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Methods: Adult neuropsychological functioning was assessed across five domains (inhibitory control, emotion recognition, decision-making, prospective memory and IQ) in 70 previously institutionalized adoptees (mean age = 25.3, 50% female) and 22 non-deprived UK adoptees (comparison group, mean age = 24.6, 41% female). ADHD and ASD symptoms were assessed using parent-completed questionnaires. Results: Early institutionalization was associated with impaired performance on all tasks in adulthood. Prospective memory deficits persisted after controlling for IQ. ADHD and ASD symptoms were positively correlated. After controlling for ASD symptoms, ADHD symptoms remained associated with deficits in IQ, prospective memory, proactive inhibition, decision-making quality and emotion recognition. ASD symptoms were not independently associated with neuropsychological deficits when accounting for their overlap with ADHD symptoms. Multiple regression analysis revealed that the link between childhood deprivation and adult ADHD symptoms was statistically explained by deprivation-related differences in adult IQ and prospective memory. Conclusions: These results represent some of the most compelling evidence to date of the enduring power of early, time-limited childhood adversity to impair long-term neuropsychological functioning across the lifespan – effects that are linked specifically to deprivation-related adult ADHD symptoms.